Facile preparation of immobilized naringinase on polyethylenimine/dopamine‐coated hydrothermal carbon spheres with high performance. Issue 8 (30th April 2021) - Zheng, Xinyu; Li, Qian; Tian, Jing; Zhan, Honglei; Yu, Chan; Wang, Shujing; Sun, Xitong; Sun, Xiyan
Abstract: BACKGROUND: Mussel‐inspired surface chemistry is recognized as a simple, efficient, and mild surface modification method, and has become a research hotspot in many fields. Hydrothermal carbon is a bio‐based material that is referred to as environmentally friendly renewable resource. In this study, the polyethylenimine (PEI)/dopamine (DA) was coated on the surface of hydrothermal carbon spheres using the co‐deposition method, making it possible to immobilize naringinase with high activity and operation stability. Subsequently, the optimal modification and immobilization conditions as well as enzyme properties were investigated. RESULTS: The naringinase activity reached up to 461.14 U g –1 carrier, which was much higher than those of the previous works. Besides, the residual naringinase activity still kept 76.44% of the initial enzyme activity after one month of storage, and maintained 62.01% of the initial enzyme activity after eight reuse cycles. CONCLUSION: Therefore, the strategy of the immobilized enzyme on PEI/DA coated hydrothermal carbon could be recognized as a promising and universal enzyme immobilization method with the advantages of high relative enzyme activity, high enzyme loading rate, high enzyme activity recovery rate, good operational stability, and facile and environmental friendly preparation route. © 2021 Society of Chemical Industry (SCI).